Detailed Analysis of the Anshan Nanguo Pear Market and Related Recommendations - Wang, Zixuan; Qian, Yahui; Zhong, Xinying; Wang, Yanuo (Asia Pacific Economic and Management Review, 2025)
The 2025 “Opinions of the Central Committee of the Communist Party of China and the State Council on Further Deepening Rural Reform and Promoting the Comprehensive Revitalization of Rural Areas” proposes to enhance the level of rural industrial development, rural construction, and rural governance, and to make every effort to increase agricultural efficiency, rural vitality, and people’s income, thereby providing a solid foundation for advancing China’s modernization. This paper aims to analyze the market customer segmentation of Nanguo Pear, enabling these nutritionally valuable pears to thrive with new vitality in the new era, and to leverage brand empowerment to uncover new product value-added potential.